Metabarcoding reveals massive species diversity of Diptera in a subtropical ecosystem. Issue 1 (23rd January 2022) - Huang, Junhao; Miao, Xiaoqian; Wang, Qingyun; Menzel, Frank; Tang, Pu; Yang, Ding; Wu, Hong; Vogler, Alfried P.
Abstract: Diptera is often considered to be the richest insect group due to its great species diversity and broad ecological versatility. However, data on dipteran diversity from subtropical ecosystems have hitherto been scarce, due to the lack of studies conducted at an appropriate large scale. We investigated the diversity and composition of Diptera communities on Tianmu Mountain, Zhejiang, China, using DNA metabarcoding technology, and evaluated their dynamic responses to the effects of slope aspect, season, and altitudinal zone. A total of 5, 092 operational taxonomic units (OTUs) were discovered and tentatively assigned to 72 dipteran families, including 2 family records new for China and 30 family records new for the locality. Cecidomyiidae, Sciaridae, and Phoridae were the predominant families, representing 53.6% of total OTUs, while 52 families include >95% unidentified and presumed undescribed species. We found that the community structure of Diptera was significantly affected by aspect, seasonality (month) and elevation, with richer diversity harbored in north‐facing than south‐facing slopes, and seasonality a more profound driver of community structure and diversity than elevation. Overall, massive species diversity of Diptera communities was discovered in this subtropical ecosystem of east China. The huge diversity of potentially undescribed species only revealed by metabarcoding now requires more detailed taxonomic study, as a step toward an evolutionary integration that accumulates information on species' geographic ranges, ecological traits, functional roles, and species interactions, and thus places the local communities in the context of the growing knowledge base of global biodiversity and its response to environmental change. Abstract : Using DNA metabarcoding technology, we investigated the diversity of Diptera communities of a subtropical ecosystem of Tianmu Mountain in eastern China. The result demonstrates the extraordinary species (5092 OTUs) and phylogenetic (72 families) diversity of Diptera, particularly in Cecidomyiidae, Sciaridae, and Phoridae that combined represented 53.6% of total OTUs, while 52 families each contained more than 95% unknown or unidentifiable species, and many more species than recognized at these sites in morphology‐based studies ("excess taxa"). The community structure of Diptera was significantly affected by aspect, seasonality, and, to a lesser extent, elevation.